Estudo das interações do lado da demanda com o mercado de energia elétrica no contexto das redes elétricas inteligentes - Carrijo, Artur da Silva (2013)
The electricity market has many participants performing various roles. In the context of Smart Grids, it expands the number of participating agents and, consequently, the number, the competition and complexity of the interactions between them. The competition allows consumersto discover and explore energy sources of low cost but requires the consumer other interactions beyond the traditional relationship with the distribution company (distco). With the redeﬁnition of the role of the consumer as a result of his active participation in the balance between supply and demand of energy, it becomes necessary to identify their interactions with the other participants, tasks, systems, subsystems and functions important to actively contribute to this balance. These interactions, called interfaces, are characterized by information that actors communicate itself to perform its functions of information collection and control tasks related to market equilibrium. The determination of these interfaces is not a trivial task because of the various alternatives for integration of the demand side. Different types and combinations of interactions between the supplier and its customers are possible. In this work will be used as a basis for discussion a concept of balance between generation and demand called homeostatic control, initially designed for a scenario of a vertically integrated monopoly. It will be studied the interactions of the consumer using the concept of homeostatic control expanded to consider the functions of demand control and integration of distributed generation and a market model that allows for consumer empowerment and within the paradigm of smart grids.